2020
DOI: 10.1051/ctv/20203501016
|View full text |Cite
|
Sign up to set email alerts
|

Climate-induced cyclical properties of regional wine production using a time-frequency approach in Douro and Minho Wine Regions

Abstract: The impact of climate on wine production (WP) temporal cycles in Douro (DR) and Vinhos Verdes (VVR) wine regions for a period of about 80 years, characterized by strong technological trend and climate variability, was modelled. The cyclical properties of WP, and which cycles are determined by spring temperature (ST) and soil water during summer (SW), were identified. It was achieved by applying a time-frequency approach, which is based on Kalman filter in the time domain. The time-varying autoregressive model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(55 reference statements)
2
3
0
Order By: Relevance
“…The current model also performs well when referring to other pollenbased models (and without the limitations mentioned above) with estimations in line with the work of Cunha et al, (Cunha et al, 1999(Cunha et al, , 2003(Cunha et al, , 2015 for the DDR. The different studies for regional-scale applications identified in the authors' previous work (Barriguinha et al, 2021) have an overall average R 2 between 0,71 and 0,99.…”
Section: Tablesupporting
confidence: 85%
See 3 more Smart Citations
“…The current model also performs well when referring to other pollenbased models (and without the limitations mentioned above) with estimations in line with the work of Cunha et al, (Cunha et al, 1999(Cunha et al, , 2003(Cunha et al, , 2015 for the DDR. The different studies for regional-scale applications identified in the authors' previous work (Barriguinha et al, 2021) have an overall average R 2 between 0,71 and 0,99.…”
Section: Tablesupporting
confidence: 85%
“…Comparing our results with the works of Cunha et al (Cunha et al, 1999(Cunha et al, , 2003, that developed and used an estimation model in the same study area (DDR) and relied on the relationship between airborne pollen and yield (Table 14), we can state that our results are very satisfactory. The pollen-based model predicts wine production for the whole DDR with a minimum and maximum threshold, and ADVID has used it since 1992 with the predictions made yearly at the VER stage.…”
Section: Tablesupporting
confidence: 77%
See 2 more Smart Citations
“…An innovative methodology to modelling the impact of climate on the wine production temporal cycles was reported by Cunha and Richter (2020); the article also shows its applicability for a period of about 80 years in two world-renowned but considerably different wine-producing regions: Douro and Vinhos Verdes. This new tool can be of great significance for planning purposes as well as for mitigation strategies facing the scenarios that combine technological progress and climate change.…”
mentioning
confidence: 98%